Exploring the nature and extent of entrepreneurial intensity in the insurance industry in hyper-inflationary Zimbabwe 2007-2010 - Janse van Vuuren, J.J. (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.